Donor–Acceptor–Acceptor's Molecules for Vacuum‐Deposited Organic Photovoltaics with Efficiency Exceeding 9%. Issue 19 (15th March 2018) - Che, Xiaozhou; Chung, Chin‐Lung; Hsu, Chou‐Chun; Liu, Feng; Wong, Ken‐Tsung; Forrest, Stephen R.
Abstract: Three vacuum‐deposited donor–acceptor–acceptor (d–a–a') small molecule donors are studied with different side chains attached to an asymmetric heterotetracene donor block for use in high efficiency organic photovoltaics (OPVs). The donor with an isobutyl side chain yields the highest crystal packing density compared to molecules with 2‐ethylhexyl or n ‐butyl chains, leading to the largest absorption coefficient and short circuit current in an OPV. It also exhibits a higher fill factor, consistent with its preferred out‐of‐plane molecular π–π stacking arrangement that facilitates charge transport in the direction perpendicular to the substrate. A power conversion efficiency of 9.3 ± 0.5% is achieved under 1 sun intensity, AM 1.5 G simulated solar illumination, which is significantly higher than 7.5 ± 0.4% of the other two molecules. These results indicate that side chain modification of d–a–a' small molecules offers an effective approach to control the crystal packing configuration, thereby improving the device performance. Abstract : Three vacuum‐deposited donor–acceptor–acceptor's small molecule donors with different alkyl chain configurations (R1 –R3 ) are synthesized and characterized to understand the side chain effect on organic photovoltaic (OPV) performance. The donor with an isobutyl (R3 ) chain yields the highest crystal packing density and largest short circuit current among the three molecules. Its preferred face‐on molecular stacking orientation on the substrate leads to the highest fill factor. The optimized OPV structure achieves a power conversion efficiency (PCE) = 9.3 ± 0.5%.